Does the eversion technique have a lower early postoperative stroke rate than the conventional technique in carotid endarterectomy?. (September 2022) - Abdel Rahim, Ahmed; Elsamani, Kareemaldin; Galal, Ali Mahmoud; Hammoda, Mohamed Ibrahim; Mittapalli, Devender
Abstract: A best evidence topic has been constructed using a described protocol. The three-part question addressed was: In carotid surgery, Does the eversion technique (ECEA) has an early postoperative lower stroke rate, As compared to conventional carotid endarterectomy (CCEA)? The outcome assessed was the stroke rate in the early potoperative period (30 days) in the two techniques. The best evidence confirmed that there is no statistically significant difference between ECEA and CCEA regarding the early postoperative stroke incidence. Highlights: Eversion technique and conventional endarterectomy are the main surgical endarterectomy techniques in carotid artery disease. There is no difference between the Eversion and conventional endarterectomy techniques in early postoperative stroke rates. Lack of randomised controlled trials that compare the two techniques.